2011
DOI: 10.1517/13543784.2011.602064
|View full text |Cite
|
Sign up to set email alerts
|

Crotamine toxicity and efficacy in mouse models of melanoma

Abstract: These data warrant further exploration of crotamine as a tumor inhibition compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 41 publications
0
54
0
2
Order By: Relevance
“…Previous studies have shown that naturally occurring CAPs such as the cell-penetrating peptide, crotamine, display potent cytotoxic activity against B16 melanoma cells in vitro as well as B16 melanomas established in syngeneic mice [38]. In the present study, the antitumor effect of LTX-315 against the highly aggressive and low immunogenic B16 melanoma cell line [39] was studied.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have shown that naturally occurring CAPs such as the cell-penetrating peptide, crotamine, display potent cytotoxic activity against B16 melanoma cells in vitro as well as B16 melanomas established in syngeneic mice [38]. In the present study, the antitumor effect of LTX-315 against the highly aggressive and low immunogenic B16 melanoma cell line [39] was studied.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence indicates that K V channel activity is a critical regulator of tumor cell proliferation by membrane polarization (Wang et al, 2004;Pardo et al, 2005). Thus, if crotamine acts on K V 1.3 in nontoxic concentration to humans, it might also be involved with the previously reported efficacy as an antitumoral agent against several aggressive tumorigenic cell lineages, such as murine melanoma cells (B16-F10), human skin melanoma cells (SK-MEL-28), and pancreatic carcinoma cell line (MIA PaCa-2) (Pereira et al, 2011).…”
Section: Crotamine Pharmacology Revisited Through K V Channel Inhibitmentioning
confidence: 99%
“…The toxin induces cell death in a dose-dependent manner in several actively proliferating cancer cells, but not in normal cells (Pereira et al, 2011). Crotamine cytotoxicity is related to the disruption of lysosomes and the activation of intracellular proteases (Hayashi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%